ANALISA KEBUTUHAN DAYA MOTOR BAKAR PADA MESIN PEMISAH TANGKAI PADI - Haafizh Arrahman, Amar Ma’ruf; Permatasari, Intan; Omardo, Masria; Haritsah A, M.; Pristiansyah, Pristiansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The rapid advancement of technology demands innovations that can improve efficiency in terms of time, labor, and cost. Manual rice separation remains a challenge for farmers as it requires significant time and effort. A rice separator machine is an agricultural tool designed to mechanically separate rice from its stalks, replacing traditional methods such as beating (gebotan) or trampling. In Riau Silip District, Bangka Belitung, the total rice field area reached 190 hectares in 2024, with a rice production of approximately 75,644 tons. With such a harvest volume, the machines currently available in the village are unable to separate the rice from the stalks optimally due to insufficient engine power, which often causes jamming and reduced torque. Therefore, we propose replacing the engine with a 11 HP motor to increase torque and separation speed. As a result, the rice stalk separator machine will have a capacity of 20 kg/hour in accordance with the desired specifications, enabling farmers to overcome obstacles and maintain the stability of their harvest yields.